Spray dried plasma protein improves digestibility in chick starter diets - L.E. Russell; J.M. Campbell; J. Polo; C.M. Parsons (Journal of Applied Poultry Research)
SUMMARY: This experiment was designed to determine the effect of spray dried animal plasma (SDAP) on digestibility of a corn-soybean meal diet in Ross 308 male broiler chicks. Two corn-soybean meal diets were formulated, a Control diet and one with 2% SDAP. Treatment (Trt) 1 and 2 were fed the Control and SDAP diet for 10 d while Trt 3 and 4 were fed the Control and SDAP diet for 21 d. Growth performance and nutrient digestibility was determined at 10 d and 21 d. By d 21, dietary treatment did not affect (P > 0.10) growth performance (BW, FI, G/F). At both 10 d and 21 d, SDAP improved (P < 0.05) digestibility of AMEn, DM and organic matter (OM). Digestibility of EE was reduced (P < 0.05) on d10 but not (P > 0.10) on d21. The addition of SDAP improved (P < 0.05) Cys digestibility on d 10 while on d 21 the addition of SDAP improved digestibility of Pro, Ala, Cys, Leu, Thr, Trp, Tyr, Val (P < 0.05) and Ser (P < 0.10). Previously published amino acid digestibility coefficients (determined in 21 d chicks) for individual ingredients (corn, soybean meal and SDAP) were used to calculate expected AA digestibility of the experimental diets and then compared to 21 d digestibility coefficients measured in the current experiment. Cystine digestibility (21 d) in the SDAP fed chicks was greater (P < 0.10) than that expected based on digestibility coefficients of individual ingredients. These data demonstrate that SDAP is a highly digestible ingredient in broiler chick diets, and it may improve digestibility of a corn-soybean meal diet fed to broiler chicks.